2018
DOI: 10.7150/thno.25025
|View full text |Cite
|
Sign up to set email alerts
|

WNT6 is a novel oncogenic prognostic biomarker in human glioblastoma

Abstract: Glioblastoma (GBM) is a universally fatal brain cancer, for which novel therapies targeting specific underlying oncogenic events are urgently needed. While the WNT pathway has been shown to be frequently activated in GBM, constituting a potential therapeutic target, the relevance of WNT6, an activator of this pathway, remains unknown.Methods: WNT6 protein and mRNA levels were evaluated in GBM. WNT6 levels were silenced or overexpressed in GBM cells to assess functional effects in vitro and in vivo. Phospho-kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 70 publications
1
47
0
Order By: Relevance
“…Whether this mechanism also occurs or is deregulated in glioma remains to be explored. Recently, Gonçalves et al [184] demonstrated that WNT6, a ligand and activator of the WNT pathway, which displays oncogenic functions in GBM [185], is transcriptionally regulated by HOXA9, identifying a novel link between HOX and WNT signalling.…”
Section: Hoxa5mentioning
confidence: 99%
“…Whether this mechanism also occurs or is deregulated in glioma remains to be explored. Recently, Gonçalves et al [184] demonstrated that WNT6, a ligand and activator of the WNT pathway, which displays oncogenic functions in GBM [185], is transcriptionally regulated by HOXA9, identifying a novel link between HOX and WNT signalling.…”
Section: Hoxa5mentioning
confidence: 99%
“…). Interestingly, when performing GSEA to identify transcriptomic signatures reminiscent of WNT6 ‐associated genes in GBM patients (Gonçalves et al , ), we found that WNT6 ‐negatively correlated genes were enriched for genes upregulated in LAML cells upon HOXA9 knockdown [enrichment score (ES) = −0.26 and false discovery rate, FDR = 0.18; Fig. ], further supporting this novel molecular link between HOXA9 and WNT6.…”
Section: Resultsmentioning
confidence: 99%
“…In 1982, for the first time, Nusse and Varmus described WNT-1 (Int-1) as an oncogene in mouse mammary tumors [35]. Up to now, increasing evidences suggested that defective WNT signaling is a causative factor in various cancers including breast cancer [36][37][38], lung cancer [39], pancreas cancer [40], colorectal cancer [41], hepatocellular carcinoma [42] and as well as glioma [6,8,14]. Despite the fact that some members of WNTs have been confirmed to play crucial roles in glioma, our study is first to investigate expression patterns, prognostic significance, and potential function of all the 19 WNT family members in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, WNT5A was found to induce rapid growth and migration of glioma and associated with the presence of tumor-associated microglia [8,9,13,14]. WNT6 expression was shown to increase the features of glioma aggressiveness [6]. WNT7A and WNT7B was shown to regulate glioma-vascular interactions [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation